Rno_circRNA_016194 might be involved in the testicular injury induced by long-term formaldehyde exposure via rno-miR-449a-5p mediated Atg4b activation. (September 2021) - Ge, Pan; Zhang, Xiang; Yang, Yan-qi; Lv, Mo-qi; Zhang, Jian; Han, Shui-ping; Zhao, Wen-bao; Zhou, Dang-xia
Abstract: Although circular RNAs (circRNAs) can function as microRNAs (miRNAs) sponges to participate in spermatogenesis, little is known about the functions of circRNAs in testis exposed to formaldehyde. In this study, twenty-four male SD rats (6–8 weeks) were randomly assigned to four groups, including a control group, 0.5, 2.46, and 5 mg/m 3 formaldehyde exposure groups, inhaling formaldehyde for eight consecutive weeks. The RT-qPCR was used to detect the expression of rno_circRNA_016194; the testicular injuries were observed by testicular histopathology. Our study illustrated up-regulated rno_circRNA_016194 was dose-dependent with formaldehyde. Simultaneously, the testicular histopathology showed an obvious damages in the 2.46 and 5 mg/m 3 formaldehyde exposure rats. Combined with bioinformatics analysis, the rno-miR-449a-5p was predicted and verified that its expression decreased in the testis exposed to formaldehyde. Meanwhile, the testicular morphometry changes were contrary to the expression of rno_circRNA_016194 and consistent with rno-miR-449a-5p. Moreover, bioinformatics analysis also prompted the potential downstream target gene for rno_circRNA_016194/rno-miR-449a-5p was Atg4b, and Atg4b expression was up-regulated in rats exposed to formaldehyde verifying by Western blot. Collectively, the rno_circRNA_016194 might be involved in formaldehyde-induced male reproductive toxicity and become potential therapeutic targets for male occupational exposure to formaldehyde. Highlights: CircRNA participates in multiple functions in testicular tissue. Formaldehyde exposure impairs testicular function in males. Autophagy is involved in testicular injury induced by formaldehyde exposure.